New species and new distribution records in Rhinotragini (Coleoptera: Cerambycidae: Cerambycinae) - Bezark, Larry G.; Martins, Ubirajara R.; Santos-Silva, Antonio; Berkov, Amy (Zootaxa, 2013)
Five new species are described: Eclipta ficta from Costa Rica; Eclipta lucida from Panama and Costa Rica; Odontocera cinctura from Costa Rica; Odontocera limula from Costa Rica, and Odontocera bettyae from Ecuador. The following five new country records are reported: Ischasia mareki Peñaherrera-Leiva & Tavakilian, 2004 from Brazil; Odontocera barn-ouini Peñaherrera-Leiva & Tavakilian, 2003, from Peru; Odontocera furcifera Bates, 1870 from Bolivia; Odontocera ni-griclavis Bates, 1873 from Argentina; Phygopoides talisiaphila Peñaherrera-Leiva & Tavakilian, 2003 from Brazil. New state records are reported for the following seven species in Brazil: Corallancyla neotropica Tippmann, 1960 from Paraná; Odontocera furcifera Bates from Amazonas; Odontocera globicollis Zajciw, 1971 from Rondônia; Odontocera punctata (Klug, 1825), from Rondônia; Odontocera trisignata Gounelle, 1911 from Pará; Pseudacorethra zischkai (Tippmann, 1960) from Amapá, Pará and Maranhão; Tomopterus clavicornis Magno, 1995 from Amazonas. Host plants are reported for Eclipta lucida, and mitochondrial-DNA sequence data are used to investigate the possibility that specimens with color polymorphism represent cryptic species.